EXPERIENCE OF ENDOSCOPIC TREATMENT OF PATIENTS WITH CHOLELITHIASIS COMPLICATED BY THE PATHOLOGY OF THE EXTRAVENOUS BILETARY DUCTS IN THE CITY OF NOVOKUZNETSK - Плюснин, Руслан Алексеевич; Снигирев, Алексей Юрьевич; Алексеев, Николай Анатольевич; Снигирев, Юрий Владимирович; Леонтьев, Антон Сергеевич; Воробей, Александр Николаевич; Баранов, Андрей Игоревич (Medicine in Kuzbass, 2019)
Retrospective analysis of surgical treatment of gallstone disease complicated by extrahepatic bile duct pathology in surgical hospitals of the city of Novokuznetsk for the period from 2016 to 2018. Objective – сomparative analysis of the results of surgical treatment of gallstone disease complicated by extrahepatic bile duct pathology in surgical hospitals of the city of Novokuznetsk. Methods. Surgical treatment of gallstone disease complicated by extrahepatic bile duct pathologywas performed using retrograde endoscopic papillosphincterotomy (REPST) and intraoperative antegrade endoscopic papillosphincterotomy (IAEPST). Results. In the Novokuznetsk City Clinical Hospital N 1, surgical treatment of gallstone disease complicated by extrahepatic bile duct pathology was performed in 185 patients. For the correction of the pathology applied REPST. Complications developed in 18 (9.7 %) patients. Novokuznetsk City Clinical Hospital N 29, surgical treatmentof gallstone disease complicated by extrahepatic bile duct pathologywas carried out using REPST in 273 patients. Complications developed in 28 (10.3 %) patients. Novokuznetsk City Clinical Hospital N 5 treatment of gallstone disease complicated by extrahepatic bile duct pathology was performed in 319 patients. IAEPST was performed in 177 patients, of REPST in 142 patients. With IAEPST, complications developed in 3 (1.6 %) patients, and when performing REPST in 5 (3.5 %) patients. Conclusion. The use of IAEPS reduces the number of post-manipulation complications. In a planned manner, the IAEPST is an operation of choice in patients with JCB with complicated pathology of VZhP and is applicable in 90.3 % of cases.